-2(4x-1)+9=-8x+11

Simple and best practice solution for -2(4x-1)+9=-8x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4x-1)+9=-8x+11 equation:


Simplifying
-2(4x + -1) + 9 = -8x + 11

Reorder the terms:
-2(-1 + 4x) + 9 = -8x + 11
(-1 * -2 + 4x * -2) + 9 = -8x + 11
(2 + -8x) + 9 = -8x + 11

Reorder the terms:
2 + 9 + -8x = -8x + 11

Combine like terms: 2 + 9 = 11
11 + -8x = -8x + 11

Reorder the terms:
11 + -8x = 11 + -8x

Add '-11' to each side of the equation.
11 + -11 + -8x = 11 + -11 + -8x

Combine like terms: 11 + -11 = 0
0 + -8x = 11 + -11 + -8x
-8x = 11 + -11 + -8x

Combine like terms: 11 + -11 = 0
-8x = 0 + -8x
-8x = -8x

Add '8x' to each side of the equation.
-8x + 8x = -8x + 8x

Combine like terms: -8x + 8x = 0
0 = -8x + 8x

Combine like terms: -8x + 8x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| .3x+5.35=9 | | 3x^2(2-x+4x^2)= | | 3x+3=3(x+8) | | -5w=10/7 | | -7w/9=-35 | | 5/6x+7/8-3/7x | | 6+2/3(12) | | -3/8w=-12 | | 4(x-1)+7=2x+2(1-x) | | -9y-9=8y+25 | | .3x+5.35=7 | | -7/8=w-2 | | .3x+5.35=6.88 | | -1/4+v=2/5 | | 10*t=5.8392 | | 3+12f=30 | | (1/10)x-11=(3/5)x | | 0.75t-0.85=0.66t | | 4+6f=24 | | 0.75t-0.85=0.6t | | 2+12f=24 | | 5x-3=4-3x | | 0.3(5)+5.35=y | | 41.6=r+9.2 | | 0.3(3)+5.35=y | | 2+9f=18 | | 2+6f=18 | | 3+6f=18 | | 3+5f=15 | | 33*17= | | 0.3(1)+5.35=y | | x=-6/2/3 |

Equations solver categories